2013
DOI: 10.1111/j.1469-0691.2012.03910.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Clostridium difficile infections in a tertiary-care hospital in Korea

Abstract: To survey healthcare-associated Clostridium difficile infection (HA-CDI) in a 900-bed tertiary-care hospital, we prospectively investigated the epidemiology of CDI and distribution of PCR-ribotypes. From February 2009 through January 2010, all patients with HA-CDI were enrolled. Epidemiological information and prescription records for antibiotics were collected. The C. difficile isolates were characterized using reference strains and were tested for antibiotic susceptibility. During the survey, incidence of HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 29 publications
5
57
2
Order By: Relevance
“…Recently, Kim et al found that ribotypes 018, 017, and 001 are predominant in humans in Korea (15), with RT078 being the most common binary toxin-positive strain in Korea (3.1%); this is consistent with other reports that indicate the worldwide prevalence of RT078 in community (14). In this study, only RT078 was identified, consistent with the predominance of this ribotype in pigs worldwide (5).…”
Section: Resultssupporting
confidence: 91%
“…Recently, Kim et al found that ribotypes 018, 017, and 001 are predominant in humans in Korea (15), with RT078 being the most common binary toxin-positive strain in Korea (3.1%); this is consistent with other reports that indicate the worldwide prevalence of RT078 in community (14). In this study, only RT078 was identified, consistent with the predominance of this ribotype in pigs worldwide (5).…”
Section: Resultssupporting
confidence: 91%
“…018, 017, and 014, while the other half comprised a broad spectrum of ribotypes. PCR ribotype 001, which is the prevalent type in Europe, was not identified in Korea in either study, whereas PCR ribotype 014 was one of the dominant strains, as in Western countries and other regions of east Asia [2,5]. In this study, there was no PCR ribotype 027, a representative hypervirulent type.…”
Section: Molecular Epidemiology Of Toxigenic Clostridium Difficile Iscontrasting
confidence: 66%
“…A partially deleted toxin A gene that could not be amplified using commercial real-time PCR was detected in six specimens (8·96%), which were all PCR ribotype 017 known to be prevalent in east Asia [4,5]. We therefore suggest that any PCR ribotype 017 strain described as toxin A negative and B positive be examined carefully to confirm whether it really lacks the toxin A gene or has a partially deleted toxin A gene that is not detected with commercial kits, as shown here [4].…”
Section: Molecular Epidemiology Of Toxigenic Clostridium Difficile Ismentioning
confidence: 99%
“…It is anaerobic and spore-forming bacteria. It usually colonizes in intestinal tract and serves as part of normal microbiota [24]. Diseases caused by toxins produced by C. difficile are colitis and it is responsible for 15%-25% cases of diarrhea.…”
Section: Clostridium Difficile (C Difficile)mentioning
confidence: 99%